Synergistic Effect of Chloride and Bromide Ions on Corrosion Inhibition of Steel in 1 mol L–1 Phosphoric Acid Using Cationic Gemini Surfactant - Wu1, Zhen-Yu; Fang1, Zheng; Zhang2, Wang; Jiang2, Xia; Qiu2, Ling-Guang (Asian Journal of Chemistry, 2011)
Synergism effect of a cationic gemini surfactant, 1,2-ethane-bis(dimethyl dodecyl ammonium bromide) (12-2-12), and halide ion (Br– or Cl–) for corrosion inhibition of cold rolled steel in 1.0 mol L-1 phosphoric acid was investigated by using weight loss, potentiodynamic polarization and electrochemical impedance spectroscopy (EIS) methods. Some thermodynamic parameters were calculated by fitting experimental data with Langmuir model. Potentiodynamic polarization studies reveal that the inhibition species is a mixed-type inhibitor. electrochemical impedance spectroscopy measurements suggest that the presence of inhibitor molecules in acidic solution decreases double layer capacitance and increases the charge transfer resistance, indicating the formation of a protective layer on steel surface.